A kind of high entropy alloy particle without carbon base loading and its preparation method and application
By alloying platinum with inexpensive transition metals, high-entropy alloy particles without carbon-based loading are solved, the problems of low efficiency and poor stability of platinum catalysts in hydrogen fuel cells are achieved, and the efficiency of platinum is achieved, and the activity and stability of the catalyst are improved.
Patent Information
- Application Number
- CN202210647425.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-06-09
AI Technical Summary
In existing hydrogen fuel cells, the cathode oxygen reduction reaction kinetics process is slow, and high load of precious metal platinum is needed as a catalyst. However, the reserves of platinum catalysts are scarce and expensive. In the long-term and harsh working conditions, the catalyst performance is severely attenuated, making it difficult for hydrogen fuel cells to achieve large-scale commercialization.
By alloying platinum with inexpensive transition metals, high-entropy alloy particles are formed, and high-entropy alloy particles are used as catalysts for preparation by two-solvent method and high-temperature reduction method, the size and structure of nanoparticles are controlled, and the utilization rate and catalytic activity of platinum are improved.
The efficient utilization of platinum is achieved, the activity and stability of the catalyst is improved, the initial mass activity reaches 4 times that of commercial Pt/C, and the activity retention rate can reach 84.2% after 5000 cycles of the stability test cycle.
Smart Images

Figure CN115172783B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell materials, and more specifically to a high entropy alloy particle without carbon-based loading, and a preparation method and application thereof. Background Art
[0002] In order to cope with the continuous growth of energy demand and environmental pollution, accelerating the development of new energy has become a common choice for countries around the world to maintain energy security, meet climate change, and achieve sustainable development. As a green energy conversion device, hydrogen fuel cells have the advantages of high energy conversion efficiency, low environmental pollution, and high specific energy.
[0003] However, in the electrode reactions of hydrogen-oxygen fuel cells, the kinetic process of the cathode oxygen reduction reaction is very slow, and a high load of precious metal platinum is required as a catalyst to ensure power output efficiency; but the reserves of precious metal platinum are scarce and expensive, and under long-term harsh operating conditions, the oxidation dissolution, agglomeration, and poisoning of the platinum catalyst accelerate its performance degradation, which makes it difficult to achieve large-scale commercialization of hydrogen fuel cells due to their high costs.
[0004] In view of the above problems, the study proposes to improve the activity and stability of Pt-based catalysts by alloying the precious metal Pt with cheap transition metals (Co, Ni, Fe, Cu, etc.) to form binary and ternary alloys, while effectively reducing the amount of Pt. In order to further improve the utilization rate of Pt, the design concept of binary alloys is extended to multi-principal alloys, and then the concept of high entropy alloys is proposed. The prior art discloses a method for preparing a monodisperse platinum-based high entropy alloy nanoparticle catalyst, and there are also reports disclosing a carbon-supported metal catalyst and its preparation method and application. Although the above-mentioned prior art improves the utilization rate of Pt and obtains a high entropy alloy catalyst with good dispersibility and good catalytic performance, they are all carbon-based catalysts with carbon materials as carriers. However, the corrosion resistance of carbon materials is poor, and Pt nanoparticles gradually accumulate and grow during the operation of the battery, resulting in lower and lower catalyst activity.
[0005] In response to the problem of carbon-based supported catalysts, the prior art discloses a method for preparing a platinum-based high entropy alloy catalyst, which is synthesized by ultrasound-assisted chemical reduction to achieve a one-pot step-by-step synthesis of high entropy alloy core nanoparticles and Pt shells. However, this method requires the use of a surfactant and a low reaction temperature, resulting in a low degree of alloying of the resulting material, and the particle size control of the high entropy alloy catalyst cannot be achieved, resulting in poor catalytic performance of the platinum-based high entropy alloy catalyst.
[0006] Therefore, it is necessary to develop high entropy alloy particles without carbon base support with better catalytic performance. Summary of the invention
[0007] The present invention provides a high entropy alloy particle without carbon-based loading in order to overcome the defect of poor catalytic performance described in the above-mentioned prior art.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned high entropy alloy particles without carbon-based loading.
[0009] Another object of the present invention is to provide an application of the above-mentioned high entropy alloy particles without carbon-based support.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0011] A carbon-free high entropy alloy particle comprises platinum, iron, cobalt, nickel and copper in a molar ratio of 1:(0.5-2):(0.5-2):(0.5-2):(0.5-2);
[0012] The high entropy alloy particles are single-phase solid solution alloys with a face-centered cubic structure;
[0013] The particle size of the high entropy alloy particles is 4 to 20 nm.
[0014] The high entropy alloy particles of the present invention use carbon-free materials as carriers, and five metal elements, platinum, iron, cobalt, nickel and copper, are evenly dispersed in a nearly equimolar ratio to form a highly single-phase solid solution structure without aggregation or segregation of individual elements.
[0015] The average particle size of high-entropy alloy particles is 8.8 to 11.2 nm. As a nano-sized alloy material, high-entropy alloy particles have extremely high utilization rate of platinum atoms and can expose more highly active edge reaction sites, thereby improving the activity of the catalyst.
[0016] Preferably, the particle size of the high entropy alloy particles is 4 to 13 nm.
[0017] Preferably, the molar ratio of platinum, iron, cobalt, nickel and copper is 1:1:1:1:1.
[0018] Preferably, the D90 particle size of the high entropy alloy particles is 12.9 nm.
[0019] The present invention also protects a method for preparing the above-mentioned high entropy alloy particles, comprising the following steps:
[0020] S1. introducing a metal salt precursor solution of platinum, iron, cobalt, nickel, or copper into the ordered pores of the molecular sieve by a two-solvent method, stirring, and drying to obtain a metal salt-molecular sieve precursor;
[0021] S2. by reducing the metal salt - molecular sieve precursor to obtain platinum iron cobalt nickel copper - molecular sieve;
[0022] The reducing atmosphere is an argon-hydrogen mixed gas, the reducing temperature is 400-1000°C, and the program heating rate is 0.5-5°C / min;
[0023] S3. The molecular sieve template is removed by etching with a hydrofluoric acid solution to obtain high entropy alloy particles without carbon-based loading.
[0024] The preparation method of the present invention controls the final size of the nanoparticles by controlling the programmed temperature rise rate of high-temperature reduction and regulating the release rate of metal salt-bound water and gas products. Small-sized nanoparticles can greatly improve the utilization rate of platinum atoms, expose more highly active edge reaction sites, and thus improve the catalyst activity.
[0025] During the high-temperature reduction process, as the temperature gradually increases, the metal salt will go through three stages, namely, the melting of the metal salt, the loss of bound water, and finally thermal decomposition and release of gas products. When the reaction temperature reaches the melting point of the metal salt, the metal salt begins to melt and exists in the molecular sieve pores in liquid form, and it can flow relatively freely in the molecular sieve pores. The faster the heating rate, the faster the bound water and gas products escape from the molecular sieve pores at the same time. Part of the liquid metal salt is squeezed out of the molecular sieve pores, and the particle size is larger and more uneven. The reduction temperature significantly affects the crystal structure of the alloy. The higher the reduction temperature, the higher the degree of alloying of the alloy.
[0026] In addition, molecular sieves were used as hard templates, and metal salt precursors were introduced into the ordered pores of the molecular sieves through a two-solvent method. The ordered pore structure of the molecular sieves was utilized to adjust the particle size of the high-entropy alloy particles and effectively limit the agglomeration of the high-entropy alloy particles.
[0027] Through hydrofluoric acid etching, on the one hand, the molecular sieve can be removed, and on the other hand, the transition metals iron, cobalt, nickel, and copper on the surface of the alloy nanoparticles can be selectively dissolved, forming more defect sites such as steps, holes, and edges on the surface of the nanoparticles, further increasing the surface density of low-coordination active sites and greatly improving the efficiency of the catalytic reaction.
[0028] In the present invention, the two-solvent method uses a two-solvent system of cyclohexane and water. Specifically, it can be: a certain mass of molecular sieve template is evenly dispersed in a non-polar solvent cyclohexane, based on the pore volume of a given mass of molecular sieve, and then an equal volume of metal salt precursor solution is slowly added dropwise. Since cyclohexane is immiscible with water and cannot dissolve metal salts, the high interfacial tension between cyclohexane and the aqueous solution is used to drive, and combined with ultrasonic dispersion, to achieve full and uniform impregnation of the molecular sieve pores with the metal salt precursor aqueous solution.
[0029] Preferably, the intake rate of the argon-hydrogen mixed gas is 50 mL / min.
[0030] Preferably, the volume ratio of hydrogen to argon in the reducing atmosphere is 5:95.
[0031] Preferably, the pore size of the molecular sieve is 6-10 nm and the pore volume is 0.5-1.5 cm 3 / g.
[0032] Preferably, the metal salt precursor solution of platinum, iron, cobalt, nickel and copper is an aqueous solution of chloroplatinic acid, iron nitrate, cobalt nitrate, nickel nitrate and copper nitrate.
[0033] Preferably, the concentration of the metal salt precursor solution is 1 to 30 wt.%, more preferably, the concentration of the metal salt precursor solution is 5 to 20 wt.%, and further preferably, the concentration of the metal salt precursor solution is 10 to 15 wt.%.
[0034] Preferably, the mass volume ratio of the molecular sieve to the metal salt precursor solution is 0.5-1 g: 0.5-1 ml.
[0035] More preferably, the mass volume ratio of the molecular sieve to the metal salt precursor solution is 1 g: 1 ml.
[0036] Preferably, the drying is carried out in a blast drying oven, the drying temperature is 60° C. to 100° C., and the drying time is 12 to 24 hours.
[0037] Preferably, the reduction time is 0.5 to 10 hours.
[0038] Preferably, the reduction temperature is 600-1000° C., and the programmed heating rate is 1-2° C. / min.
[0039] More preferably, the reduction temperature is 900° C. and the programmed heating rate is 1° C. / min.
[0040] Preferably, the concentration of the hydrofluoric acid solution is 4 to 40 wt.%, and the etching treatment time is 8 to 36 hours.
[0041] More preferably, the etching treatment time is 10 to 24 hours; further preferably, the etching treatment time is 12 to 20 hours.
[0042] The present invention also protects the use of the high entropy alloy particles as redox catalysts in oxygen reduction electrocatalytic reactions in acidic systems.
[0043] Specifically, high entropy alloy particles can be used as redox catalysts and applied to the cathode of fuel cells to catalyze oxygen reduction reactions.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The present invention develops a carbon-free high entropy alloy particle with the advantages of low Pt loading, high Pt utilization, high catalytic activity and high stability. The high entropy alloy particle is used as an oxygen reduction catalyst, and the initial mass activity reaches 0.57Amg Pt -1 , which is about 4 times that of commercial Pt / C. After 5000 cycles of stability test, the activity retention rate can reach 84.2%.
[0046] The present invention controls the high-temperature reduction heating rate and regulates the release rate of metal salt-bound water and gas products to accurately regulate the final size of the nanoparticles. Small-sized nanoparticles can greatly improve the utilization rate of platinum atoms and expose more highly active edge reaction sites. While removing the molecular sieve through hydrofluoric acid etching, the transition metals iron, cobalt, nickel, and copper on the surface of the alloy nanoparticles can also be selectively dissolved to form more defect sites such as steps, holes, and edges on the surface of the nanoparticles, further increasing the surface density of low-coordinated active sites, thereby improving the catalytic activity of the high-entropy alloy particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is a flow chart for preparing high entropy alloy nanoparticles of the present invention;
[0048] Figure 2 This is a transmission electron microscope image of the platinum-iron-cobalt-nickel-copper molecular sieve prepared in step S2 of Example 1;
[0049] Figure 3 TEM image of the high entropy alloy particles prepared in Example 1;
[0050] Figure 4 This is an EDS-Mapping diagram of the high entropy alloy particles prepared in Example 1;
[0051] Figure 5 The oxygen reduction polarization curve of the high entropy alloy particles prepared in Example 1 as a catalyst and the commercial platinum carbon catalyst Pt / C;
[0052] Figure 6 The polarization curves of the high entropy alloy particles prepared in Example 1 as catalysts before and after 5000 cycles of cycle stability testing;
[0053] Figure 7 Schematic diagram of mass specific activity and area specific activity of the high entropy alloy particles prepared in Example 1 as a catalyst before and after 5000 cycles of cyclic stability testing;
[0054] Figure 8 X-ray diffraction patterns of high entropy alloy particles of Example 1, Example 2, Example 3 and Comparative Example 2;
[0055] Fig. 9The oxygen reduction polarization curves of high entropy alloy particles and commercial pt / C of Example 1, Example 2, Example 3, Comparative Example 2 are shown;
[0056] Fig.10 Graphs showing the oxygen reduction polarization curves of the high entropy alloy particles of Example 1, Example 4, and Comparative Example 1. DETAILED DESCRIPTION
[0057] The present invention will be further described below in conjunction with specific implementation modes.
[0058] The raw materials in the embodiments and comparative examples can be obtained from commercial sources, among which:
[0059] Molecular sieve-1, purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd., SBA15 molecular sieve, pore size 6-10 nm, pore volume 1 cm 3 / g;
[0060] Molecular sieve-2, purchased from Aladdin Reagent Co., Ltd., KIT-6 molecular sieve, average pore size 9.2nm, pore volume 0.5~1.5cm 3 / g;
[0061] Chloroplatinic acid hexahydrate, ferric nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, and copper nitrate trihydrate were purchased from Aladdin Reagent Co., Ltd.
[0062] Commercial Pt / C was purchased from John Matthey Company.
[0063] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.
[0064] Example 1
[0065] This embodiment provides a high entropy alloy particle, and the preparation method includes the following steps:
[0066] S1. 1 g of SBA15 molecular sieve (molecular sieve-1, pore size 6-10 nm, pore volume 1 cm 3 / g) and 30ml cyclohexane are added into a beaker, stirred and ultrasonically treated to form a uniform suspension; then, under stirring, 1ml of a metal salt precursor solution (containing an aqueous solution of 9.5mg hexahydrate chloroplatinic acid (H2PtCl6·6H2O), 5.6mg copper nitrate trihydrate (Cu(NO3)2·3H2O), 9.3mg ferric nitrate nonahydrate (Fe(NO3)2·9H2O), 6.7mg cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6.7mg nickel nitrate hexahydrate (Ni(NO3)2·6H2O)) is added dropwise into the beaker, ultrasonicated for half an hour to evenly disperse the components, and then stirred until the solvent is completely volatilized to obtain a metal salt-molecular sieve precursor;
[0067] S2. The metal salt-molecular sieve precursor is evenly spread into the corundum ark, and placed in a tube furnace for high-temperature thermal reduction. Before heating, an argon-hydrogen mixed gas (the volume ratio of Ar:H2 is 95:5) is passed through for 30 minutes to exclude the air in the quartz tube, and the air intake rate is maintained at 50mL / min; then, the temperature is increased to 900℃ at a heating rate of 1℃ / min and maintained for 1h, and then naturally cooled to room temperature to obtain a platinum-iron-cobalt-nickel-copper-molecular sieve;
[0068] S3. Slowly add the above-mentioned platinum iron cobalt nickel copper molecular sieve into a centrifuge tube, add 30 ml of 4wt.% hydrofluoric acid solution, let it stand for 24 hours to remove the molecular sieve template, then centrifuge and wash it with deionized water, dry the sample at 60°C in a forced air drying oven for 24 hours, and grind the obtained sample evenly to obtain high entropy alloy particles without carbon-based load.
[0069] The platinum iron cobalt nickel copper molecular sieve obtained in step S2 is tested by transmission electron microscopy. The specific method is as follows: the microscopic morphology, crystal structure and elemental composition content of the sample are analyzed using a Tecnai G2 (F30) transmission electron microscope (TEM) of FEI Company of the Netherlands in combination with an energy dispersive spectrometer (EDS). The samples of different thicknesses and surface roughness have different scattering effects on high-energy electron beams. The related signals of the scattered electrons are collected using an electromagnetic lens and displayed on a fluorescent screen, so that the microscopic morphology of the sample can be observed. The transmission electron microscope picture is as follows Figure 2 As shown, it can be seen that the ordered pores of the molecular sieve effectively limit the agglomeration of the high entropy alloy, and the high entropy alloy is evenly dispersed.
[0070] The high entropy alloy particles prepared in step S3 are detected by transmission electron microscopy. Figure 3 It can be seen that the high entropy alloy particles are uniform in size, the particle size of the nanoparticles is distributed in the range of 4 to 15 nm, the D90 particle size is 12.9 nm, and the average particle size is 9.2 nm.
[0071] The high entropy alloy particles prepared in step S3 are subjected to X-ray energy spectrum analysis, and the EDS-Mapping diagram is as follows: Figure 4 As shown. It can be seen that the metal elements in the high entropy alloy particles prepared in this embodiment are highly evenly distributed, and no large amount of agglomeration or segregation of metal elements is found. The molar ratio of platinum, iron, cobalt, nickel, and copper is about 1:1:1:1:1. The X-ray diffraction spectrum is shown in Figure 8 As shown, it can be seen that the high entropy alloy particles are single-phase solid solution alloys with a face-centered cubic structure.
[0072] Example 2
[0073] This embodiment provides a high entropy alloy particle, and the preparation method is different from that of embodiment 1 in that:
[0074] In step S2, during the reduction treatment, the air intake rate is 50 mL / min; then, the temperature is heated to 1000° C. at a heating rate of 1° C. / min and maintained for 2 h.
[0075] The particle size distribution of the prepared high entropy alloy particles is 4-13 nm, and the average particle size is 9.5 nm.
[0076] Example 3
[0077] This embodiment provides a high entropy alloy particle, and the preparation method is different from that of embodiment 1 in that:
[0078] In step S2, during the reduction treatment, the air intake rate is 50 mL / min; then, the temperature is heated to 800° C. at a heating rate of 1° C. / min and maintained for 3 h.
[0079] The particle size distribution of the prepared high entropy alloy particles is 4-13 nm, and the average particle size is 9.1 nm.
[0080] Example 4
[0081] This embodiment provides a high entropy alloy particle, and the preparation method is different from that of embodiment 1 in that:
[0082] In step S2, during the reduction treatment, the air intake rate is 50 mL / min; then, the temperature is heated to 900° C. at a heating rate of 0.5° C. / min and maintained for 1 h.
[0083] The particle size distribution of the prepared high entropy alloy particles is 4-13 nm, and the average particle size is 8.8 nm.
[0084] Example 5
[0085] This embodiment provides a high entropy alloy particle, and the preparation method is different from that of embodiment 1 in that:
[0086] In step S2, during the reduction treatment, the air intake rate is 50 mL / min; then, the temperature is heated to 900° C. at a heating rate of 5° C. / min and maintained for 1 h.
[0087] The particle size distribution of the prepared high entropy alloy particles is 4-20 nm, and the average particle size is 11.8 nm.
[0088] Example 6
[0089] This embodiment provides a high entropy alloy particle, and the preparation method is different from that of embodiment 1 in that:
[0090] The molecular sieve used was molecular sieve-2, with a pore size of 9.2 nm and a pore volume of 0.5-1.5 cm 3 / g.
[0091] The particle size distribution of the prepared high entropy alloy particles is 4-13 nm, and the average particle size is 11.2 nm.
[0092] Comparative Example 1
[0093] This comparative example provides a high entropy alloy particle, and the preparation method is different from that of Example 1 in that:
[0094] In step S2, during the reduction treatment, the air intake rate is 50 mL / min; then, the temperature is heated to 900° C. at a heating rate of 10° C. / min and maintained for 1 h.
[0095] The particle size distribution of the prepared high entropy alloy particles is between 12 and 54 nm, and the average particle size is 45.4 nm.
[0096] Comparative Example 2
[0097] This comparative example provides a high entropy alloy particle, and the preparation method is different from that of Example 1 in that:
[0098] In step S2, during the reduction treatment, the air intake rate is 50 mL / min; then, the temperature is heated to 400° C. at a heating rate of 1° C. / min and maintained for 1 h.
[0099] The particle size distribution of the obtained high entropy alloy particles is 4 to 13 nm, and the average particle size is 9.6 nm. Figure 8 From the X-ray diffraction pattern of Comparative Example 2, it can be seen that when the reduction temperature is too low, the alloying degree of the material is too low.
[0100] Catalytic performance test
[0101] The catalytic performance of the high entropy alloy particles prepared in the above examples and comparative examples was tested, with the high entropy alloy particles as the cathode material, the platinum sheet as the anode, the saturated calomel electrode as the reference electrode, and the 0.1M HClO4 aqueous solution as the reference electrode. The specific method is as follows:
[0102] Oxygen reduction polarization curve analysis: Linear scanning voltammetry (LSV) was performed in an O2-saturated 0.1 M HClO4 aqueous solution with a potential scan range of 1.1 to 0.2 V (vs. RHE) at a scan rate of 20 mV / s and an electrode rotation speed of 1600 rpm.
[0103] Cyclic stability test: At room temperature, in an O2-saturated 0.1M HClO4 aqueous solution, the test was carried out at a scan rate of 50 mV / s in the potential range of 0.6 to 1.0 V (vs. RHE); the polarization curves and mass specific activity and area specific activity before and after 5000 cycles were detected.
[0104] Figure 5 This is the oxygen reduction polarization curve of the high entropy alloy particles prepared in Example 1 as a catalyst and the commercial platinum carbon catalyst Pt / C. It can be seen that the prepared high entropy alloy particles have more excellent oxygen reduction catalytic performance as a catalyst, with a half-wave potential of 0.892V, which is 42mV higher than that of the commercial Pt / C catalyst.
[0105] Figure 6 The polarization curves of the high entropy alloy particles prepared in Example 1 as catalysts before and after 5000 cycles of cycle stability testing; Figure 7 The figure is a schematic diagram of the mass specific activity and area specific activity of the high entropy alloy particles prepared in Example 1 as a catalyst before and after 5000 cycles of cyclic stability test. It can be found that the high entropy alloy particles are used as oxygen reduction catalysts, and the initial mass activity reaches 0.57A mg Pt -1 , which is about 4 times that of commercial Pt / C. After 5000 cycles of stability test, the half-slope potential of the high entropy alloy particles in Example 1 decreased by 11mV, and the mass specific activity and area specific activity decreased by only 15.8% and 19.2% respectively. The high entropy alloy particles showed excellent stability as a catalyst.
[0106] according to Fig. 9 and Fig.10 From the test results of the ORR polarization curve, it can be seen that the embodiments of the present application have better ORR catalytic performance than comparative examples 1 to 2 and commercial Pt / C.
[0107] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing high entropy alloy particles without carbon-based loading, characterized in that: The steps include: S1. A metal salt precursor solution containing platinum, iron, cobalt, nickel, and copper is introduced into the ordered pores of the molecular sieve by a two-solvent method, and the metal salt-molecular sieve precursor is obtained by stirring and drying; S2. By reducing the metal salt - molecular sieve precursor, a platinum iron cobalt nickel copper - molecular sieve is obtained; The reducing atmosphere is an argon-hydrogen mixed gas, the reducing temperature is 400-1000°C, and the program heating rate is 0.5-5°C / min; S3. The molecular sieve template is removed by etching with a hydrofluoric acid solution to obtain high entropy alloy particles without carbon-based loading. The high entropy alloy particles include platinum, iron, cobalt, nickel, and copper in a molar ratio of 1: (0.5-2): (0.5-2): (0.5-2): (0.5-2); The high entropy alloy particles are single-phase solid solution alloys with a face-centered cubic structure; The particle size of the high entropy alloy particles is 4-20 nm. Among them, the two-solvent method described in S1 is a two-solvent system of cyclohexane and water. The molecular sieve is ultrasonically uniformly dispersed in the cyclohexane solution, an equal volume of metal salt precursor solution is added dropwise, and the metal salt precursor solutions of platinum, iron, cobalt, nickel, and copper are introduced into the ordered channels of the molecular sieve by combining ultrasonic dispersion.
2. The preparation method according to claim 1, characterized in that: The molar ratio of platinum, iron, cobalt, nickel and copper is 1:1:1:1:
1.
3. The preparation method according to claim 1, characterized in that: The average particle size of the high entropy alloy particles is 8.8-11.2 nm.
4. The preparation method according to claim 1, characterized in that: The volume ratio of hydrogen to argon in the reducing atmosphere is 5:
95.
5. The preparation method according to claim 1, characterized in that: The pore size of the molecular sieve is 6-10 nm, and the pore volume is 0.5-1.5 cm 3 / g.
6. The preparation method according to claim 1, characterized in that: The metal salt precursor solution containing platinum, iron, cobalt, nickel and copper is an aqueous solution of chloroplatinic acid, iron nitrate, cobalt nitrate, nickel nitrate and copper nitrate.
7. The preparation method according to claim 6, characterized in that: The concentration of the metal salt precursor solution is 1-30 wt.%.
8. The preparation method according to claim 1, characterized in that: The mass volume ratio of the molecular sieve to the metal salt precursor solution is 0.5-1 g: 0.5-1 ml.
9. The preparation method according to claim 1, characterized in that: The concentration of the hydrofluoric acid solution is 4 wt.%, and the etching treatment time is 8 to 36 hours.
Citation Information
Patent Citations
Low-temperature synthesis method and application of corrosion-resistant high-entropy alloy nano-catalyst
CN113559879A
Thermal shock synthesis of multielement nanoparticles
US20190161840A1